Environmental damage: Prevention and fight against marine pollution of ships due to hydrocarbon spills - Morillo Herrada, Zósimo Roberto (2022)
The article explores the problem of environmental damage in reference to the  prevention and fight against marine pollution of ships due to dumping of  hydrocarbons. The theoretical framework used is that of international environmental  law, international maritime law and the internal regulations of the States in these areas.  In particular, the agreements within the framework of the International Maritime  Organization, the Permanent Commission of the South Pacific, the European Union  and Peru are analyzed. In the Peruvian case, the General Law of the Environment is  analyzed and the processes in the civil, criminal and administrative spheres are described, in cases of environmental damage.